2021
DOI: 10.3389/fpubh.2021.761765
|View full text |Cite
|
Sign up to set email alerts
|

Lower Back Pain as an Occupational Hazard Among Ugandan Health Workers

Abstract: Background: Lower back pain is a public health concern affecting 70–85% of the world's population. There is paucity of published data on the prevalence, disability and risk factors for lower back pain among health workers in Uganda.Objective: To determine the frequency rate (note that is it implicit that frequency is a rate like incidence so including rate seems redundant here. This is bounded by zero and infinity. In contrast, prevalence is bounded by 0 and 1 and is thus a proportion not a rate) of lower back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This could be due to the fact that these studies all had a higher sample size than the current study and used diverse populations from both private and public hospital laboratories. The prevalence (39.6%) established in a cross sectional descriptive study conducted among 245 health care workers at Arua general hospital (15) was within the con dence interval of the current study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This could be due to the fact that these studies all had a higher sample size than the current study and used diverse populations from both private and public hospital laboratories. The prevalence (39.6%) established in a cross sectional descriptive study conducted among 245 health care workers at Arua general hospital (15) was within the con dence interval of the current study.…”
Section: Discussionsupporting
confidence: 64%
“…Working in the same position for long can cause muscular fatigue and low back pain due to stretching and compressing of the tendons and nerves (24). Data from various studies among different occupational groups indicated a signi cant association between awkward postures, repetitious tasks, over standing with MSDs both separately and in combination ( 27) and (15).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The time taken for completion of the survey ranged from 1 to 15 min (median time 2 min). One-fifth of respondents (10 individuals) claimed that by completing The sample size for the current cross-sectional study was calculated to be representative based on previous studies (24)(25)(26) and our pilot study carried out on a group of 50 participants. In the pilot study, the Kish-Leslie formula (25) was used to determine the sample size sufficient for validating the findings.…”
Section: Questionnairementioning
confidence: 99%
“…6 Lack of training in pain management resulted in doctors and nurses evaluating patients too late following surgery and providing insufficient pain management. 64 The International Association for the Study of Pain, which includes members representing >200 countries, has determined the necessity for healthcare professionals to increase their knowledge of postoperative pain management. Therefore, rearranging the priority of resource allocation and conducting pertinent organizational seminars regularly is important in a clinical setting with heavily constrained resources in order to ensure that medical workers are up to date with the current trends.…”
Section: Insufficient Knowledge Of Medical Staffmentioning
confidence: 99%